Pancreatic serous cystadenoma case report of conservative approach - De La Cruz Hernandez, Samantha Jazmin; Silva Martinez, Juan Pedro; Alvarez Yeomans, Daniel; Morales Cardona, Antonio; Palomares Leal, Alain (International Surgery Journal, 2023)
There are multiples pancreatic tumors, some of them being benign some being malignant, some more frequent than others, such as pancreatic pseudocyst and serous cystic neoplasm, in this case it’s about the last one witch is the most common cystic neoplasm of the pancreas about 30%, the initial approach to this type of tumors its either CT scan or MRI, which will show the honeycomb-like pattern, which is pathognomonic of this neoplasm, and the treatment options depend on the symptoms that produce.